ANALYSIS OF THE STRESS STATE VARIABLES FOR UNSATURATED SOILS WITH COMPRESSIBLE AND INCOMPRESSIBLE SOIL SOLIDS - Krisnanto, Sugeng; Sella Ananda Rifdah; Agil Akmal Ananda; Nurul Aulia Putri (GEOMATE Journal, 2025)
Net normal stress, (s - ua) and matric suction, (ua - uw) are the stress state variables for unsaturated soils. Stress state variables are the state of stresses in soil that govern the shear strength and the volume change of the soil. Considering the fundamental role of the stress state variables, the correctness of their theoretical derivation is therefore fundamental. In addition, the need to consider the compressibility of the soil solids is recommended in the literature. However, the existing theoretical derivation of stress state variables does not convey a clear explanation for the conditions of compressible and incompressible soil solids. In this paper, a detailed derivation and explanation of the stress state variable for unsaturated soils is presented. The derivation is started from an equilibrium of an unsaturated soil element. The distinction between unsaturated soils with compressible solids and those with incompressible solids is clearly explained. Thus, the derivation in this paper improves the existing theoretical derivation. From the theoretical derivation, the stress state variables for unsaturated soils with incompressible soil solids are the net normal stress, (s - ua) and the matric suction, (ua - uw). For unsaturated soils with compressible soil solids, an additional stress state variable is the pore-air pressure, ua. The theoretical derivation in this paper better explains the stress state variables for unsaturated soils. This is essential because the net normal stress and the matric suction have been used in various analyses of unsaturated soils.